Innovative Integral Educational Leadership in the Superior Normal Schools of Colombia - Novoa-Palacios, Amparo (2020)
The article analyzes the experience of eleven coordinators from the Superior Normal Schools of Colombia (ENS). They enrolled in the Educational Social Innovation Program. The goal is to study their perception of educational leadership based on values and innovation. The methodology used is the systematization of experiences, with a qualitative approach that articulates descriptive research and the method of research and documentary analysis. The results were obtained through the conceptual, comparative, and relational analysis of eleven leaders-coordinators’ contributions from the Superior Normal Schools. In these institutions, the analysis identified some aspects characterizing the innovative educational integral leader as someone who contributes to solving socio-educational problems. These can be solved from responses located in the territory and from a sense of belonging that integrates the different spheres of life experience. This means prioritizing dialogue and solidarity and assuming tension and conflict as part of ongoing learning from an axiological framework. Likewise, the analysis found that the territory, the educational projects, and the strengthening of community-based competencies constitute aspects that make an integral, innovative, educational leader someone capable of combining community methodologies based on in-depth knowledge of the communities’ problems.